Implementasi Program Berbasis Masjid di Desa Margo Mulyo Kecamatan Pondok Kubang Kabupaten Bengkulu Tengah - Dedi Efrizal; Arli Julian Ansyori; yuni, Sri Wahyuni; Amiza Fransiska; Nur Dina Rahmah (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This community service project focuses on the revitalization of Masjid Miftahul Huda in Desa Margo Mulyo, Kecamatan Pondok Kubang, Bengkulu Tengah, through a mosque-based KKN (Kuliah Kerja Nyata) program. The primary issues identified include low youth participation in religious and social activities, inadequate Quranic reading skills among children and adolescents, and limited awareness of cleanliness and health within the community. The program aims to address these issues by implementing a series of integrated activities, including Islamic New Year celebrations, educational outreach to local schools, regular mosque cleaning initiatives, Quranic reading enhancement programs, and monthly health exercise sessions. The approach taken is participatory, involving the active engagement of the community in all activities. The results indicate a significant increase in community involvement, particularly among the youth, in mosque-centered activities. There is also a noticeable improvement in Quranic literacy and heightened awareness of cleanliness and health within the village. The findings underscore the effectiveness of community-based approaches in enhancing social and religious life in rural settings.